The secret history of Bigfoot : field notes on a North American monster - O'Connor, John (Journalist) (Sourcebooks, 2024)
Bigfoot is an instantly recognizable figure. Through the decades, this elusive primate has been featured in movies and books, on coffee mugs, beer koozies, car polish, and CBD oil. Which begs the question: what is it about Bigfoot that's caught hold of our imaginations? Journalist and self-diagnosed skeptic John O'Connor is fascinated by Sasquatch. Curious to learn more, he embarks on a quest through the North American wilds in search of Bigfoot, its myth and meaning. Alongside an eccentric cast of characters, he explores the zany and secretive world of "cryptozoology," tracking Bigfoot through ancient folklore to Harry and the Hendersons, while examining the forces behind our ever-widening belief in the supernatural. As O'Connor treks through the shrouded forests of the Pacific Northwest, listens to firsthand accounts, and attends Bigfoot conventions, he's left wondering--what happens when the lines between myth and reality blur? Perfect for fans of Bill Bryson and Douglas Preston, and with sharp wit and an adventurous spirit, this heartfelt exploration of a cornerstone of American folklore unpacks why we believe in the things that we do, what that says about us, and how it shapes our world. --